A Provable Secure Image Encryption Schema Based on Fractional Order Chaotic Systems - Aydin, Yilmaz; Ozkaynak, Fatih (Ieee, 2019)
In the literature, many chaotic systems have been used in the design of image encryption algorithms. In this study, an application of fractional order chaotic systems is investigated. The aim of the study is to improve the disadvantageous aspects of existing methods based on discrete and continuous time chaotic systems by utilizing the features of fractional order chaotic systems. The most important advantage of the study compared to the literature is that the proposed encryption algorithm is designed with a provable security approach. Analyses results have been shown that the proposed method can be used successfully in many information security applications.
23rd International Conference on Electronics -- JUN 17-19, 2019 -- Kaunas Univ Technol, Palanga, LITHUANIA
Keywords: Chaos; Cryptography; Fractional order chaos; Image encryption; Nonlinear signal processing